Administration of Nitrates After Spontaneous Delivery in Rheumatic Heart Disease - Koeshardiandi, Mirza; Himawan, Muhammad Wildan Afif; Perdhana, Fajar; Wicaksana, Zulfikar Loka (Faculty of Medicine-Universitas Airlangga, 2023)
Introduction: Heart disease is one of the most common causes of maternal death. The incidence has increased since women with congenital and acquired heart disease reached fertile age. The circulation system changes during pregnancy which are induced by changes in the progesterone. The changes in progesterone levels increase heart work and cause death in pregnant women. Objective: This report aims to elaborate on the administration of nitrates as the management of labor in rheumatic heart disease (RHD). Case Report: A 27-year-old woman complained of shortness of breath and wanted to give birth. The patient was 38 weeks pregnant and had a history of heart disease. Antero-posterior chest radiography examination showed pulmonary edema and cardiomegaly. The patient was examined using echocardiography before spontaneous labor and was diagnosed as pregnant with rheumatic heart disease. As an emergency management, the patient was given painless spontaneous labor. The patient was given nitrates on the first day after delivery as a treatment for progesterone withdrawal syndrome in this case. After the delivery process was completed, the patient was admitted to the Intensive Care Unit (ICU). Progesterone hormone produced by the corpus luteum and the placenta until the eighth week of pregnancy and before delivery, respectively, can reduce systemic vascular resistance. Progesterone hormone increase causes peripheral vasodilation by affecting the function of endothelial nitric oxide synthase (eNOS) and nitrite oxide (NO) production. Conclusion: A pregnant woman with rheumatic heart disease can be given exogenous nitrate. Administration of exogenous nitrates in this patient successfully prevent the reduction of peripheral vascular resistance and postpartum hemodynamic instability because it can replace the reduction in nitric oxide caused by progesterone withdrawal.